Renal denervation: potential impact on hypertension in kidney disease? - Blankestijn, Peter J.; Ritz, Eberhard (Nephrology, dialysis, transplantation, 2011)
About a year ago, the introduction of catheter-based renal denervation was briefly mentioned in an editorial in Nephrology Dialysis Transplantation [1]. In view of recent new data, it is appropriate to discuss this novel method and its implications in kidney disease in greater detail. In the following, we shall briefly discuss the underlying rationale, the potential clinical relevance and some unresolved issues.
Gesehen am 30.03.2022